The sad story of Burton, Speke, and the Nile ; or, was John Hanning Speke a cad? : looking at the evidence - Carnochan, W. B. (Stanford General Books, 2006)
This is a study of the famous controversy between Richard Burton and John Hanning Speke, fellow explorers who quarreled over Speke's claim to have discovered the source of the Nile during their African expedition in 1857-59. Speke died of a gunshot wound, probably accidental, the day before a scheduled debate with Burton in 1864. Burton has had the upper hand in subsequent accounts. Speke has been called a "cad." In light of new evidence and after a careful reading of duelling texts, Carnochan concludes that the case against Speke remains unproven-and that the story, as normally told, displays the inescapable uncertainty of historical narrative. All was fair in this love-war.